Conquest and Care for the Preservation of Nature and Environment in the Novel Amba by Laksmi Pamuntjak: Study Ecocriticism - Wiyatmi Wiyatmi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This study aims to analyse (1) how the characters in the novel Amba by Laksmi Pamuntjak conquest and care for the preservation of nature and environment, and (2) the depiction of nature and the environment in relation to the overall story of Amba using ecocriticism perspective. The results are as follows. First, the nature and the environment of Buru are described as an arena to be conquered by the main character (Bhishma), who was a political prisoner in the New Order era. In addition, the preservation of nature and environment of Buru Island also should be protected from exploitation, especially by outsiders who came to the island of Buru. Second, the depiction of nature and the environment in Amba is related to the creation of the setting of story (place and time), i.e. Buru Island as political prisoners’ detention place in the New Order era, between 1969–2006. From the perspective of ecocriticism these findings demonstrate how an island that was secluded so used to dispose of political prisoners have experienced the dynamics of an arena which was originally a natural and fierce, eventually turned into an island that invites entrants to explore and exploit natural wealth, so must be preserved.